Corona-Finanzhilfen des Bundes zur Entlastung der Kommunen - Thomas Döring (Wirtschaftsdienst, 2020)
Die Corona-Krise hat bei den Kommunen zu zusätzlichen Ausgaben und hohen Steuerausfällen geführt. Zur Stabilisierung der Kommunalfinanzen hat der Bund zwei Gesetzesinitiativen auf den Weg gebracht. Neben einer dauerhaft stärkeren Beteiligung des Bundes an den Kosten für Unterkunft und Heizung in der Grundsicherung für Arbeitssuchende sollen einmalig und in pauschaler Form die krisenbedingten Gewerbesteuermindereinnahmen der Kommunen kompensiert werden. Beide Maßnahmen führen jedoch zu einer unsachgerechten Vermischung von kurzfristigen Interventionen zur fiskalischen Bewältigung der Corona-Krise mit grundlegenden Reformnotwendigkeiten der Kommunalfinanzen. – – The Corona crisis has led to unforeseeable additional expenses as well as significant losses of tax income for local governments. In order to stabilise public finances at the local level, the German federal government has passed two new bills. One of the bills basically provides for a permanent expansion of the federal government's financial contribution towards the cost of housing and heating as part of the guaranteed minimum income for job seekers. The federal government also singularly compensates - in cooperation with the state governments - local governments for the significant crisis-related decline in local business tax revenue through a lump sum payment in 2020. However, these two measures will affect short-term intervention to cope with the fiscal problems of the Corona crisis as well as the fundamental need to reform public finances at local government level.
Keywords: H70; H79; 330